Islamic Education in the Society 5.0 Era: Lesson to Learn - Hasanah, Uswatun; Hakim, Istiazah Ulima; Zain, Zaki Faddad Syarif (IJECA (International Journal of Education and Curriculum Application), 2023)
The Society 5.0 era presents challenges to all sectors of people's lives including the Islamic education sector, so that it requires in-depth studies related to Islamic education in the 5.0 era. Therefore, this study aims to determine the future direction of Islamic Education in the 50-era. The descriptive qualitative method was employed, with library research as the type of study. The writers did not conduct fieldwork when looking for data sources, instead relying on textual sources. The data-gathering technique utilized was based on the type of inquiry: documentation. Furthermore, the collected data was examined utilizing content analysis techniques. The analysis results show that the development in Islamic Education focuses on actors, namely teachers and policymakers by facilitating a fun learning process and paying attention to student wellbeing, planting and strengthening Islamic characters, and raising students' awareness of the importance of science and technology in the future, particularly in the era of society. 5.0 and realizing autonomous learning. So it can be concluded, Islamic Education can contribute to preparing excellent human resources with various skills that are relevant to the needs of the era if Islamic Education can adapt to change and doesn’t lose its essence.